Geopolitics of Brazil and the theoretical and ideological debate on the coup of 1964 and the military dictatorship - Almeida, Lúcio Flávio Rodrigues de (Pontifícia Universidade Católica de São Paulo, 2014)
This article is an attempt to contribute to the theoretical debate on the 1964 coup and themilitary dictatorship, especially with regard to the ideological dimension. In this preliminarywork, the role of the Superior War College, and especially its principle doctrinal exponent,Golbery do Couto e Silva, are analyzed, with a focus on a single book, Geopolitics of Brazil.